POST-PANDEMIC AGE: WORLD HEALTH ORGANIZATION (WHO) AND GLOBAL WORLD HEALTH GOVERNANCE FROM THE PERSPECTIVE OF NEOREALISM AND NEOLIBERALISM - Ramadhan , Iqbal (Journal of Social Political Sciences, 2023)
The Covid-19 pandemic has brought disaster and catastrophe to humanity's survival. The Covid-19 pandemic has paralyzed not only society's standard social order, but also a country's political and economic stability. On the other hand, the outbreak has altered the global health order. The Covid-19 pandemic has pushed international organizations such as the World Health Organization (WHO) to take the lead in fighting the outbreak. WHO, as a key player in the global health order, is responsible for preventing pandemics like Covid-19 from recurring in the future. The author intends to examine the role of WHO in compiling global health governance through the lens of the two primary schools of International Relations, neorealism and neoliberalism, in this scientific article. At the discussion stage, the author employs a qualitative method supported by secondary data to support the argument. At the analysis stage, the author contends that there are two opposing viewpoints on WHO's role in developing global health governance. The role of the WHO is viewed skeptically by neorealism, which believes that countries can only rely on themselves to overcome a future pandemic threat. On the contrary, the neoliberalism viewpoint encourages countries to actively participate in global health governance by collaborating with WHO. The author concludes that the state must continue to develop its capabilities in order to survive another pandemic. Countries, on the other hand, must collaborate with international organizational actors to develop inclusive and adaptive global health governance